Pemberdayaan Masyarakat Berbasis Potensi Lokal Dalam Upaya Meningkatkan Perekonomian Keluarga Didesa Telaga Waru Kecamatan Labuapi - Baiq Ismiwati; Taufiq Chaidir; Ida Ayu Putri S (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2023)
Villages as governments that clearly understand the potential of both natural resources and human resources are expected to be economically independent. Developing village potential can encourage the independence of village/district communities through developing superior potential and strengthening institutions and empowering the community. The main source of livelihood for the residents of Telaga Waru Hamlet is as construction workers and domestic servants, although in fact this village has several potentials that can be used as a business base to earn income. However, this cannot be utilized by the population due to the limited abilities and knowledge they have. In general, the average Telaga Waru hamlet/village community does not know much about what economic potential they actually have in their hamlet/village and what efforts can be made to increase their family income. For this reason, it is very relevant to carry out community empowerment based on local potential for mothers and young women in Telaga Waru Hamlet. The method of implementing community service used is firstly observing targets related to economic conditions and economic activities. Second, delivering outreach material which includes identifying the economic potential of the hamlet/village, business motivation and revolving fund management, which is then continued by identifying what they know that can used as a business base in their hamlet/village and the last is the formation of a business group. The results of the service show that 1) The potential of the hamlet which can be used as a basis/resource to be managed and cultivated by the community is very minimal, but in the hamlet/village of Telaga Waru there is an afternoon market which can be said to be a potential place for trading and at the same time for purchasing various necessities. needed for merchandise. 2) It was identified that the average education of mothers in Telaga Waru Hamlet was low, thus influencing their way of thinking about progressing and developing. 3) The lack of business capital owned by partners, thus hampering the partners' willingness and enthusiasm to try to improve their economic conditions. 4) there is a strong commitment from partners to manage the revolving funds provided by the Team so that it is hoped that it can help partners' business capital.